STUDI FENOMENOLOGI HYPERHONEST PADA MEDIA SOSIAL INSTAGRAM MAHASISWA FUAD IAIN PAREPARE - Hastuti, Sri; Qadaruddin, Muhammad; Annisa, Nur (Communication and Islamic Broadcasting Studies IAIN Parepare, 2025)
Abstract The purpose of this study is to explore the form of expression regulation of FUAD students' hyperhonest on Instagram media, to describe the motives of FUAD students' hyperhonest on Instagram media, and to measure the impact of FUAD students' hyperhonest on Instagram media. The method used is a descriptive qualitative method using a phenomenological approach to explore students' in-depth experiences related to hyperhonest on Instagram media. Data collection techniques through observation, interviews, and documentation. Data analysis techniques by means of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are, (1) Many FUAD students like to express themselves on Instagram media. Students share moments and feelings, spontaneously and transparently, both sad and happy (over disclosure). Many express themselves through photos, videos with captions, while some use quotes or backsound according to the student's condition. (2) Some FUAD students choose to use a second account to express themselves which can only be accessed by certain people. Students feel more comfortable, free, and satisfied when expressing themselves on Instagram. Instagram media is also used as a place to store moments that have been done. (3) The impact of FUAD students' hyperhonest on Instagram media gets support and positive suggestions from followers, some also get hate speech, body shaming and bullying which have a negative impact on students' lives.